A construção de uma vida digna e a batalha por legitimidade moral: fronteiras simbólicas no Programa Bolsa Família - Machado, Nínive Fonseca (2020)
This work seeks to analyze how beneficiaries from the Bolsa Família Program define moral values and cultural repertoires in shaping symbolic boundaries between them and other social groups. Considering the constant dissemination of criticisms and negative images in the public debate around the Bolsa Família Program since its creation, this research intends to identify, from the beneficiaries‘ perspective, what are the values mobilized by them that guide their actions and give them meaning to their lives, as well as, what makes them approach or to be apart from other social groups. If, on the one hand, the criticisms (and their corresponding stereotypes) of this policy are very visible, on the other hand, we still know very little about how the beneficiaries themselves conceive issues related to poverty, or even if they mobilize others elements in the process of signifying their own beneficiary status. The data discussed here are the result of fieldwork carried out in a poor neighborhood in the city of João Pessoa, Brazil, and the constant relationship of this reality with the literature produced on poverty, inequality, social policies, and morality. With the sad reality of being one of the most unequal countries in the world, the discussion brought up along the chapters goes back to the tragic Brazilian history of being able to perpetuate alarming rates of poverty and the consequent strategies used by society to make this situation invisible. As a way of 'attacking' the problem, countless narratives have appeared throughout history targeting the reasons that would make Brazil so poor and so unequal over generations. These explanations are usually loaded with moral judgments and also subsidized by economical explanations that do nothing more than transferring to the poor the responsibility for their own situations. It is in this context that this work seeks to understand how beneficiaries elaborate on their narratives, considering that the image commonly associated with them is related to lazy and full of children kind of people. One of the results of this research is that the beneficiaries, unlike the image conveyed about them, feel that being a beneficiary is, in fact, an achievement for those who strive for it, and not a guaranteed social right. For them, in order to be able to be a beneficiary, a person has to fight to get in and later, fight to maintain it since to remain as a beneficiary means complying with the rules established by the government. Their moral rules value the correct, fair, and dignified style of life, and what makes the beneficiaries closer or not to other people is not the fact that they are beneficiaries of the same program, but if the others share the same ethical and moral values as they do. The negative images conveyed about the beneficiaries in general (lazy and full of children) are also shared by the interviewees, however, always in relation to the other beneficiaries, and never to themselves. In this sense, I conclude that the constant criticisms that supposedly targets technical aspects of the program are, in fact, criticisms targeting the behavior of the poor women who are beneficiaries, and that the impact of these negative images reflects in the formation of the beneficiaries' own opinion about their actions, as well as, the moral judgment they make about the actions of other beneficiaries.